Analysis of Net Asset Value-based Projected Performance of Sharia Mutual Funds Post Covid - Rijal Anshori, Arif; Siti Rohmah Maulida, Ira; Dewi Himayasari, Neng (KnE Social Sciences, 2023)
As we know that the Covid-19 pandemic has affected the financial markets and banking sectors; however, it is different from the non-banking financial institutions having Sharia mutual funds. In 2019, the net asset value (NAV) of Sharia mutual funds were about 53,735.58, while in 2020 it increased to 74,367.44. Seeing the above phenomenon, mutual funds are one of the strategies that can be an investment opportunity and can be a safe investment alternative for capital owners, especially small capital owners and owners who do not have much time and expertise to calculate the return and risk on their investment. This study aims to examine the projections of the financial performance of Sharia mutual funds for the next 6 years. The method used is quantitative with a descriptive approach, data processing was done by projection analysis using Excel. The results of this study are the performance of Islamic mutual funds during the early post-Covid era, from May to the present, that has decreased to an asset value of 42,668.70 caused by withdrawal for Hajj funds, inflation, etc. The cause of the decline is in line with the theory above that Islamic mutual funds can be affected by unsystematic risk, which is impacted by the value of securities in the stock market that fluctuates according to general economic conditions. There is also a projected performance of Sharia mutual funds based on the NAV of the post-Covid era for the next 6 years that will continue to increase, reaching the highest point in 2027 of 102,054.28. Keywords: mutual fund, Sharia, net asset value